Microphase separation of short wormlike diblock copolymers with a finite interaction range - Jiang, Ying; Zhang, Xinghua; Miao, Bing; Yan, Dadong; Chen, Jeff Z. Y (Soft matter, 2016)
We investigate several structural properties of low-molecular weight AB diblock copolymer melts, focusing on a number of features that substantially deviate from those of high-molecular weight copolymer melts. The study is based on the wormlike chain formalism aided by random phase approximation and self-consistent field theory. We examine the effects that stemmed from both the finite molecular weight and the finite interaction range between unlike AB monomers. The latter yields profound effects on systems consisting of short wormlike block copolymers. The noticeable shift of the order-disorder transition point is discussed. Attention is also paid to the strong-segregation regime, where low molecular weight polymers are subject to finite stretchability. A study on the structural properties of low-molecular weight AB diblock copolymers indicates substantial deviations from the properties of high-molecular weight polymers.